Ionothermal Syntheses, Crystal Structures, and Chemical Bonding of the Rhodium-Centered Clusters [RhBi9]4+ and [(RhBi7)I8] - Groh, Matthias F.; Mueller, Ulrike; Isaeva, Anna; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2017)
The first filled Bi9 5+ polycation was isolated in the form of [RhBi9](AlCl4)4 crystals by dissolution of the solid precursor Bi12–xRhX13–x in the Lewis-acidic ionic liquid [BMIm]Cl·3.6AlCl3 (BMIm = 1-butyl-3-methylimidazolium) at 140 °C. In the monoclinic crystal structure [P21/n, a = 1217.5(2) pm, b = 1741.6(3) pm, c = 5085.7(7) pm, β = 90.117(8)°], the almost spherical [RhBi9]4+ polycations (approximate D3h symmetry; Rh–Bi 276 ± 3 pm) show pronounced orientational disorder. Shiny black needles of Bi7RhI8 were obtained from the reaction of rhodium, bismuth, and BiI3 in the ionic liquid [BMIm]Cl·1.3AlCl3 at 200 °C. Bi7RhI8 [P21/n, a = 943.10(1) pm, b = 1582.40(1) pm, c = 1645.40(1) pm, β = 95.48(1)°] is isostructural to Bi7RhBr8 and consists of molecular clusters [(RhBi7)I8]. The rhodium atom centers a pentagonal bipyramid of bismuth atoms, and the two apical bismuth atoms are in square-planar coordination of iodide ions. DFT-based calculations indicate strong bismuth-rhodium bonding with predominantly covalent character for both clusters. The electronic structure of the Bi9 5+ cage is notably modified by this interaction, but the characteristic bonding features of the host cluster with the D3h configuration are still maintained. In Bi7RhI8, on the other hand, bonding is dictated by the spatial distribution of mutually repelling iodine atoms, and the Bi–Rh bonding is highly polar.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Bismuth; Cluster compounds; Endohedral atoms; Intermetalloid clusters; Ionic liquids